Respostas
respondido por:
1
é só substituir cada valor de X na expressão
para x= -2
y=(-2)^2-5*(-2)+4=18
para x= -1
y=(-1)^2-5*(-1)+4=10
para x= 0
y=0^2-5*0+4=4
para x=1
y= 1^2-5*1+4=0
para x=2
y=2^2-5*2+4=-10
para x= -2
y=(-2)^2-5*(-2)+4=18
para x= -1
y=(-1)^2-5*(-1)+4=10
para x= 0
y=0^2-5*0+4=4
para x=1
y= 1^2-5*1+4=0
para x=2
y=2^2-5*2+4=-10
guiaexpansao:
Para X=2 o resultado é -10 ou -2?
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás